FACTORS THAT CAUSE TEENAGE PREGNANCY: SYSTEMATIC REVIEW - Amalia Rizqi Sholihah; Restuning Widiasih; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2021)
Teenage pregnancy continues to be a major global health problem in the world. This pregnancy occurs in adolescents aged 14-19 years, both married and unmarried. This systematic review aims to determine the factors that cause teenage pregnancy. This systematic review was conducted by searching for articles using electronic databases, namely Cocroane, Willey Online Library, Sage Journals, Cambridge, Pubmed, Science Direct. The keywords used areAND sexual behavior AND factors affect AND pregnancy AND adolescents. Search results found 12,982 articles according to keywords, namely Cocroane 74 articles, Willey Online Library 1974 articles, Sage Journals 2467 articles, Cambridge 5721 articles, Pubmed 230, Science Direct 2516 articles.After adjusting for keywords, inclusion criteria, as well as title and abstract screening, articles that answer research questions as many as 5 articles. Based on the results of the study, it was found that the factors causing teenage pregnancy were:namely a history of older sisters and mothers who have experienced teenage pregnancies, peer influence and psychological control from mothers and fathers, psychological pressure, dropping out of school, and a history of having family members who have been detained. This study provides information about the factors that cause teenage pregnancy in the world. Further studies can be carried out more deeply about the factors that cause teenage pregnancy in Indonesia.